Video Head Impulse Test in Persons with Blindness: Feasibility and Outcomes - Jha, Raghav Hira; Singh, Niraj Kumar; Kumar, Prawin (Journal of the American Academy of Audiology, 2022)
Background To achieve balance, persons with blindness (PWB) use proprioceptive and vestibular cues rather than the visual system; however, PWB are equally susceptible to acquire vestibular disorders. Reliable assessments of the vestibular system in PWB are essential to determine the presence or absence of vestibular disorders.Purpose The saccular and the utricular functioning can be assessed using cervical vestibular-evoked myogenic potential and ocular vestibular-evoked myogenic potential, respectively. Evaluation of the functional integrity of the semicircular canals requires an assessment of the vestibular ocular reflex; however, this can be challenging in PWB. Video head impulse test (vHIT) assesses the vestibular ocular reflex (VOR) elicited against the natural high-frequency head movement in the planes of all six semicircular canals. This study aimed to explore the feasibility and outcomes of administering vHIT in PWB.Research Design Standard (static) groups comparison.Study Sample Nineteen young PWB and 23 age-matched adults with “normal” vision (control group) were included in the study.Data Collection and Analyses PWB underwent vHIT once, while the control group was tested in three conditions; condition 1 was used to simulate blindness for the control group, where vHIT was done in a pitch-dark room without prior instructions; condition 2 included vHIT testing in daylight, without a fixed visual target and any instructions; and condition 3 involved vHIT in daylight in the presence of a set visual target and with standard instructions to maintain visual focus on the visual target.Results The VOR gain was abnormal in the PWB group for all the canals. Among the PWB, the lateral canals (mean = 0.63) had the best VOR gain, followed by the anterior canals (mean = 0.53) and the posterior canals (mean = 0.31). In the control group, the VOR gain was significantly reduced in condition 1. There was no significant difference between the VOR gain in the PWB group and the control group in condition 1 for the lateral and the anterior canals. A higher proportion of participants in the PWB group had the presence of refixation saccades.Conclusion VOR is significantly reduced in PWB but not completely absent. There may be a need to develop normative data for blind individuals to decide whether or not a person with blindness has a vestibular dysfunction, specifically a VOR deficit.
Keywords: PWB; simulated blindness; vHIT; VOR gain; saccades